The Effect of Celebrity Endorsement, Influencer Marketing, and Electronic Word of Mouth (E-WOM) on Online Shopping Purchase Intention with Brand Image as an Intervening Variable on TikTok Shop Users - Anggellista Permata Sari; Seprianti Eka Putri (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aims to determine the role of brand image in mediating the influence of celebrity endorsement, influencer marketing and electronic word of mouth on online shopping purchase intentions at Tiktok Shop. This study obtained a sample of 170 respondents using the non-probability sampling method. The data analysis technique in this study used PLS-SEM with the assistance program SmartPls version 3.3.7. The results of this study indicate that celebrity endorsements, influencer marketing, and electronic word of mouth have an effect on purchase intention. Celebrity endorsement, influencer marketing and electronic word of mouth have an effect on brand image. Brand image is able to mediate the influence of influencer marketing and electronic word of mouth on purchase intentions, while brand image is not able to mediate the influence of celebrity endorsements. By using celebrity endorsements and influencer marketing. In forming good electronic word of mouth, producers need convenient online media to build online with consumers.